Effectiveness of using Google Classroom in learning English: a literature review - Perumal, Thayabaran; Jalaluddin, Ilyana (Asian Scholars Network, 2023)
This literature review aims to explore the effectiveness of Google Classroom in enhancing the English language. The review examined previous studies on using Google Classroom, its features in language learning, and how they have been applied to improve English. The findings indicate that Google Classroom positively impacts students' language learning outcomes, such as improved writing, speaking, and listening skills and increased motivation and engagement. However, the effectiveness of Google Classroom depends on various factors, such as the teacher's proficiency in technology, adequate technical support, and students’ access to devices and the internet. Students’ access to devices and the internet is critical to successful implementation, especially in rural and low-income areas where access to technology can be limited. Therefore, educators and policymakers must ensure adequate resources and support are available to successfully implement Google Classroom in language learning. The review highlights the need for further research on the implementation and effectiveness of Google Classroom in language learning. Overall, this study suggests that using Google Classroom can be a valuable tool to support language learning. With the increasing demand for English language proficiency in the global job market, using technology in language learning, such as Google Classroom, can be a valuable tool to improve language learning outcomes and prepare students for future success.